Reactions of 2-[Lithio(trimethylsilyl)methyl]-2H-tetrazoles: Synthesis of 2-[1-(Trimethylsilyl)alkyl]-2H-tetrazoles and (2H-Tetrazol-2-yl)acetates - Umemoto, Hideaki; Onaka, Takuya; Miki, Yasuyoshi; Nakamura, Akira; Maegawa, Tomohiro (Synlett, 2015)
The reaction of 2-[(trimethylsilyl)methyl]-2H-tetrazoles with various alkyl halides and carbonates using n-butyllithium or lithium diisopropylamide (LDA) gave 2-[1-(trimethylsilyl)alkyl]-2H-tetrazoles and (2H-tetrazol-2-yl)acetates as useful synthons of modified tetrazoles.
Keywords: tetrazoles; synthetic methods; lithiation; synthons